Aberrant homeodomain–DNA cooperative dimerization underlies distinct developmental defects in two dominant CRX retinopathy models - Zheng, Yiqiao; Stormo, Gary D.; Chen, Shiming

(untitled) (Genome Research, 2025)
Paired-class homeodomain (HD) transcription factors (TFs) play essential roles in vertebrate development, and their mutations are linked to human diseases. One unique feature of a paired-class HD is cooperative dimerization on specific palindrome DNA sequences. Yet, the functional significance of HD cooperative dimerization in animal development and its dysregulation in diseases remains elusive. Using the retinal TF cone-rod homeobox (CRX) as a model, we have studied how blindness-causing mutations in the paired HD, p.E80A and p.K88N, alter CRX's cooperative dimerization, leading to gene misexpression and photoreceptor developmental deficits in dominant manners. CRXE80A maintains binding at monomeric WT CRX motifs but is deficient in cooperative binding at dimeric motifs. CRXE80A’s cooperativity defect impacts the exponential increase of photoreceptor gene expression in terminal differentiation and produces immature, nonfunctional photoreceptors in the CrxE80A retinas. CRXK88N is highly cooperative and localizes to ectopic genomic sites with strong enrichment of dimeric HD motifs. CRXK88N’s altered biochemical properties disrupt CRX's ability to direct dynamic chromatin remodeling during development to activate photoreceptor differentiation programs and silence progenitor programs. Our study provides in vitro and in vivo molecular evidence that paired-class HD cooperative dimerization regulates neuronal development and that dysregulation of cooperative binding contributes to severe dominant blinding retinopathies.